Algae as an ecological indicator in creating a sustainable and ecological environment - Johari, Nursyafica Nadia; Othman, Rashidi; Ismail, Muhammad Hanafi; Wan Sulaiman, Wan Syibrah Hanisah; Mohd Latiff, Nur Hanie; Mohd Hatta, Farah Ayuni; Ramya, Razanah (2023)
Environmental problems, including global warming and climate change widely acknowledged as one of the top global threats with far-reaching consequences. Despite the importance of decreasing CO2 emissions or developing carbon-free energy sources, carbon sequestration should be a key issue since the amount of carbon dioxide that already exists in the atmosphere is great enough to cause global warming. Algae can ﬁx carbon dioxide 10-50 times more than other terrestrial plants. It also has a rapid growth and multiplying rate much greater than higher plants. The study is aimed to explore algae characteristics and behaviour as potential ecological indicators and sequester agents for an unhealthy environment in an urban context. It was conducted by cultivating algae in controlled environments, which include different formulations, photoperiod and pH. Then, the selected species of algae will be evaluated and compared for their efficiency as potential carbon sequestration agents and lastly, to identify the colour changes of the algae that indicate the surrounding environment. These algae will be optimized and applied in landscape ecological design as phycoindicator and as a phycosequestration. Besides being a marker in creating a sustainable and ecological environment, it could help reduce the planet's natural impact by employing biological and sustainable initiatives that are aligned with the objectives of maqasid shariah. The principle of Al Darra Yuzal is very close to prevent all kinds of harm in order to protect human life, wealth as well as a future environment for the next generation as what is being concluded in the objectives of shariah.